2022
DOI: 10.3390/ijerph19126987
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Mapping of the Phytoremediation of Cadmium-Contaminated Soil: A Bibliometric Analysis from 1994 to 2021

Abstract: Cadmium pollution of soil threatens the environmental quality and human health. Phytoremediation of cadmium-contaminated soil has attracted global attention in recent decades. This study aimed to conduct a comprehensive and systematic review of the literature on phytoremediation of cadmium-contaminated soil based on bibliometric analysis. A total of 5494 articles published between 1994 and 2021 were retrieved from the Web of Science Core Collection. Our knowledge mapping presented the authors, journals, countr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 107 publications
0
1
0
Order By: Relevance
“…Ecological pollution by the heavy metal cadmium has attracted extensive attention worldwide [ 31 , 32 , 33 ]. Studies have shown that under cadmium stress conditions in the soil, plants are subjected to the toxic effects of heavy metals, leading to adverse effects on growth, photosynthetic activity, and antioxidant enzyme activity [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ecological pollution by the heavy metal cadmium has attracted extensive attention worldwide [ 31 , 32 , 33 ]. Studies have shown that under cadmium stress conditions in the soil, plants are subjected to the toxic effects of heavy metals, leading to adverse effects on growth, photosynthetic activity, and antioxidant enzyme activity [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%